The Application of Multimodal Approach in the “English for Nusantara” Coursebook for 8th Graders - Dwi Herwindha Mahanani; Sri Wahyuni; Zulfa Sakhiyya (Universitas Negeri Semarang, 2025)
The use of multimodal resources is increasingly essential in the developing field of education, particularly in foreign language learning. Textual materials alone can hardly meet the varied needs of learners; the principle of multimodality gives a richer experience through text, pictures, color, and symbols as well as layout. It is out of this requirement that the Indonesian government issued the English for Nusantara coursebook for 8th graders under the Merdeka Curriculum. This study discovered how multimodality is applied in the coursebook, focusing on Chapter 2, Kindness Begins with Me. Using descriptive qualitative methods and documentation techniques, the analysis applies Kress and van Leeuwen’s (2006) framework of visual grammar consisting of representational, interactive, and compositional aspects. Results indicate that the coursebook has systematically put in multimodal elements towards guiding and getting students engaged. Human and non-human visuals deliver moral values; interactive elements evoke an emotional connection; strategic layout pushes message clarity. Such mode works hand-in-hand to better both language skills and character education. The study recommends similar multimodal approaches be adopted in other educational materials for creating learning experiences that are more inclusive and meaningful for junior high school students.